Review on eye-hand span in sight-reading of music - Joris Perra; Bénédicte Poulin-Charronnat; Thierry Baccino; Véronique Drai-Zerbib (Bern Open Publishing, 2021)
In a sight-reading task, the position of the eyes on the score is generally further ahead than the note being produced by the instrument. This anticipation allows musicians to identify the upcoming notes and possible difficulties and to plan their gestures accordingly. The eye-hand span (EHS) corresponds to this offset between the eye and the hand and measures the distance or latency between an eye fixation on the score and the production of the note on the instrument. While EHS is mostly quite short, the variation in its size can depend on multiple factors. EHS increases in line with the musician's expertise level, diminishes as a function of the complexity of the score and can vary depending on the context in which it is played. By summarizing the main factors that affect EHS and the methodologies used in this field of study, the present review of the literature highlights the fact that a) to ensure effective sight reading, the EHS must be adaptable and optimized in size (neither too long not too short), with the best sight readers exhibiting a high level of perceptual flexibility in adapting their span to the complexity of the score; b) it is important to interpret EHS in the light of the specificities of the score, given that it varies so much both within and between scores; and c) the flexibility of EHS can be a good indicator of the perceptual and cognitive capacities of musicians, showing that a musician's gaze can be attracted early by a complexity in a still distant part of the score. These various points are discussed in the light of the literature on music-reading expertise. Promising avenues of research using the eye tracking method are proposed in order to further our knowledge of the construction of an expertise that requires multisensory integration.